Epistemologi Fikih Filantropi Masa Pandemi Covid-19 di Indonesia: The Epistemology of Fiqh Philanthropy in the Covid-19 Pandemic Period in Indonesia - Wahyu Wahyu Akbar; athoillah ismaly (Jurnal Bimas Islam, 2021)
Handling economic problems in Indonesia during the Covid-19 pandemic necessitates the importance of cooperation from all elements of society with the government in offering various alternative solutions. This study intends to explore and identify the epistemological basis of Islamic law in the construction of the Fatwa Majelis Ulama Indonesia (MUI) Nomor 23 Tahun 2020 Tentang Pemanfaatan Harta Zakat, Infak, dan Shadaqah Untuk Penanggulangan Wabah Covid-19 dan Dampaknya. This qualitative research is in the form of a literature review with a normative philosophical approach. The analytical theory used is the paradigm of idealism and realism of Islamic law. The results of the study state that the epistemological construction of Islamic law in the MUI fatwa Number 23 of 2020 tends to emphasize the idealism paradigm of Islamic law. First, universal ethical moral values ('am) which are taken from the theological text basis (nas). Second, the use of the rules of Islamic law (qawaid fiqhiyah) which emphasizes the rules of maslahah mursalah (public benefit).Third, the opinion of classical scholars.This finding shows that the presence of the MUI Fatwa in responding to contemporary problems is not always based on the realism paradigm of Islamic law, but also based on the idealism paradigm of Islamic law by making the foundations of theological normative texts and the repertoire of classical fiqh thought as the epistemological basis of its fatwa, as well as in addressing socio-economic problems that arise. caused by the Covid-19 pandemic in Indonesia.